Usefulness of Interest Income Sensitivity Disclosures - Cheng, Mei; Hodder, Leslie D.; Watkins, Jessica (The Accounting Review, 2021)
ABSTRACT We document multiple dimensions of usefulness of banks' interest income sensitivity disclosures. First, we find management-generated sensitivity measures are predictive of future realized changes in net interest income. Second, we find financial analysts' forecasts of net interest income reflect information provided by interest income sensitivity disclosures. Third, we find equity market responses to interest rate shocks as well as firms' interest rate betas are larger for banks with greater disclosed sensitivity of net interest income to interest rate changes. Across all of these tests, the informativeness of income sensitivity measures is incremental to that of regulatory data. These results suggest that interest income sensitivity disclosures are informative measures of interest rate risk. Our results contradict assertions that these disclosures are useless due to lack of relevance of income sensitivity, poor modeling techniques, and/or redundancy relative to regulatory data. JEL Classifications: G21; M41.